Modelling, control and performance analysis of a single‐stage single‐phase inverter with reduced low‐frequency input current ripple. Issue 6 (1st May 2018) - Shi, Youjie; Liu, Bangyin; Duan, Shanxu
Abstract : A large amount of ripple at twice the output frequency will emerge in the input current due to the pulsating output power in a single‐phase inverter. A current‐fed‐type single‐stage single‐phase inverter is investigated. Based on the switch multiplexing technique, it can realise not only dc–ac power conversion but also low‐frequency input current ripple reduction with a lower number of power switches. A control strategy is proposed, which is capable of controlling both the input and output port performance. The operation performance is analysed, including circuit parameters, efficiency and dynamic behaviour. Besides, the equivalence of control strategy and the similarity of circuit component rating are revealed between this single‐stage inverter and a conventional two‐stage inverter. The single‐stage inverter is preferred in the applications which are sensitive to the power switch number and low‐frequency input current ripple. Finally, some experimental results are performed to verify the theoretical analysis.